Microstructure and nanoscratch behavior of spark-plasma-sintered Ti-V-Al-Nb-Hf high-entropy alloy - Dewangan, Sheetal Kumar; Cheenepalli, Nagarjuna; Lee, Hansung; Ahn, Byungmin (Journal of Materials Research and Technology, 2024)
In this work, an equiatomic Ti-V-Al-Nb-Hf high-entropy alloy (HEA) was designed by thermodynamic simulation and prepared experimentally via a powder metallurgy approach. A nanoindentation and nano scratch technique was used to study the mechanical and friction behavior of the HEA. The results revealed that a nano hardness of 7.39 ± 0.4 GPa and an elastic modulus of 140.75 ± 6.3 GPa was achieved. The coefficient of friction (COF) and creep behavior of the alloy were studied by scratch tests in ramping mode under constant-loading conditions. The COF quickly increased as the normal load increased at the beginning stage of creep performance. Additionally, three-dimensional modeling was performed to obtain a graphical representation, which can be used to explore the morphology and geometry of the scratched track. From the experimental findings, the creep behavior of the alloy is classified into two separate regimes: transient and steady-state regions. The present study demonstrates the scratch and creep behavior of the HEA in the context of the scratch mechanisms.
Keywords: Coefficient of frictions; Creep behaviors; Friction behaviour; High entropy alloys; Mechanical behavior; Nano indentation; Nano-scratch; Scratch behavior; Spark plasma; Thermodynamic simulations; Friction; High entropy alloys; Microstructure; Nanoindentation; Scratch behavior